50 knitted wraps and shawls - Nöldeke, Marisa (Stackpole Books, 2020)
Which one will you knit first? With 50 patterns for knitted shawls and wraps to choose from, in so many styles, textures, and yarns, choosing your first project will be a welcome challenge. From simple knit-purl designs for beginners to slip-stitch color work designs, doubleknit, brioche, lace, and cables--there are designs to interest every level of knitter. There are so many fabulous designs, this will become your go-to shawl knitting book.